Correlation between fasting blood glucose level and risk of breast cancer in women: a single-center, prospective cohort study - Li, Gefei; Yin, Mingjie; Fan, Zhimin; Qu, Fengjiang (Frontiers in Oncology, 2024)
Purpose We prospectively analyzed the correlation between fasting plasma glucose (FPG) and the risk of breast cancer in women; explored the independent risk factors for breast cancer in women, and compared the effect of FPG level on the risk of young and non-young breast cancer. Our study provides new evidence and ideas for research into breast cancer etiology in China, improves the accuracy of secondary prevention of breast cancer, and provides options for the clinical diagnosis and treatment of breast cancer patients with diabetes. Materials and methods Three cohorts of women participating in the first health examination of the Kailuan Group in 2006, 2008 and 2010 were assembled to conduct a descriptive analysis of the baseline data on FPG. The cumulative incidence of breast cancer in different groups over 13 years was calculated using the Kaplan-Meier method and groups were compared using the log-rank test. A Cox proportional hazards regression model was used to analyze the association between FPG level and the risk of breast cancer. Results The cumulative incidence of breast cancer increased in people with FPG higher than 5.29 mmol/L, but there was no significant difference in the effect of different levels of FPG on the risk of young breast cancer in the population. Different degrees of fasting glucose can affect the risk of non-young breast cancer in the population. Conclusion The results of this study suggest that the risk of breast cancer can be reversed by early intervention to control levels of FPG. Regular monitoring of FPG may reduce the misdiagnosis rate of breast cancer in the population.